COMPARISON OF TAKLIFI LAW ON THE VIEWS OF ABU HAMID AL-GHAZALI AND ABDUL HAMID BIN AL-HUSAIN AL-SHARWANI REGARDING SHARING HAIR AND CUTTING NAILS WHEN JUNUB - Ira Maulidatul Ula; Amin Said Husni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This thesis, titled "Comparative Study of Taklifi Law on Abu Hamid Al-Ghazali and Abdul Hamid Al-Sharwani's Views on Shaving Hair and Cutting Nails during Junub," aims to answer two research questions: What are Abu Hamid Al-Ghazaliand Abdul Ḥamid Al-Sharwani's views on shaving hair and cutting nails during junub? How can the taklifi law be compared and analyzed in relation to their views?. This study employs a library research approach, gathering data from various literary sources, including books and journals. The author compares and analyzes the taklifi law in relation to Al-Ghazali and Al-Sharwāni's views on shaving hair and cutting nails during junub. The study reveals two main findings: Al-Ghazali's view, as stated in his book "Ihya’ Ulum al-Din," is that it is not advisable to shave hair or cut nails during junub, as this may lead to accountability in the afterlife. In contrast, Al-Sharwāni recommends delaying these actions until after purification. (2) The analysis of taklifi law reveals that both scholars' views imply that shaving hair and cutting nails during junub are disliked (makruh). The study concludes that both Al-Ghazali and Al-Sharwani's views on shaving hair and cutting nails during junub are similar, and it is recommended that individuals, especially the general public, gain a deeper understanding of Islamic law to avoid making hasty judgments without proper evidence.